PENGARUH PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH TERHADAP LABA PADA BANK BCA SYARIAH, BANK BNI SYARIAH, BANK BRI SYARIAH, BANK MUAMALAT, BANK SYARIAH MANDIRI DAN BANK VICTORIA SYARIAH TAHUN 2014-2018 - Riri Purnama Surya; Zainuddin Zainuddin; Himyar Pasrizal (IAIN Batusangkar, 2021)
In discussing this, the problem is how much influence mudharabah and musharaka financing have on the profit of Islamic banks. The aim is to discover the effect of mudharabah and musharaka financing on the profit of Islamic banks. This type of research is field research with a quantitative approach. The data source comes from a written document of the Financial Services Authority in published financial statements. The data analysis technique that the writer did was Classical Assumption Test, Multiple Regression, Multiple Correlation, Determination Coefficient Test (R2), Hypothesis Testing, namely T-Test and F Test. The author's research results, mudharabah financing affects earnings because it has a count of 3.675, thus t arithmetic> t table (3.675> 2.048) with a significant level of 0.001 below significant 0.05 (5%) (0.001 <0.05), then H0 is rejected, and Ha is accepted. Musharaka financing does not affect profit because it has a count of 0.288, thus t arithmetic <t table (0.288 <2.048). With a significant level of 0.776 above a significant 0.05 (5%) (0.776> 0.05), then H0 is accepted, and Ha is rejected. Mudharabah and Masyarakat financing simultaneously affect earnings because it has a count of 10.856, thus f arithmetic f table (10.856> 4.210). With a significant level of 0,000 below significant 0.05 (5%) (0,000 <0.05), then H0 is rejected and Ha is accepted.